Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Prove that CosA + CosB + CosC 3/2 for a triangle ABC ( means less than or equal to)

Prove that 
CosA + CosB + CosC  3/2 for a triangle ABC
 means less than or equal to)
 

Grade:11

3 Answers

Aziz Alam IIT Roorkee
askIITians Faculty 233 Points
6 years ago
Since C = π - A - B, we want to maximize the function:

f(A,B) = cos(A) + cos(B) + cos(π-A-B)

f(A,B) = cos(A) + cos(B) - cos(A+B)

within the region R:

A+B<π
0<A,B

Since it's an open region, we know the max cannot occur anywhere along the boundary of Rand must occur at some critical point(s) in the interior.

So we just have to find the point where the total derivative is 0. Of course, A and B aren't dependent on each other, so we can just set the two partials equal to zero to find the critical point(s):

sin(A+B) - sin(A) = 0
sin(A+B) - sin(B) = 0

So sin(A) = sin(B), thus A=B

But sin(A) = sin(2A) = 2sin(A)cos(A)

Thus cos(A) = 1/2

Note: we can divide by sin(A) because A≠0. This also excludes A=0 as a solution, since A=0 is in the boundary of R, which is not a part of our valid region.

A = π/3

So the max is at A=B=C=π/3.

Plugging that in, we know the maximum value of f is:

3cos(π/3) = 3/2

Thus for angles A,B,C of a triangle:

cos(A)+cos(B)+cos(C) = f(A,B) = ≤ 3/2 .
Avinash
52 Points
3 years ago
Let cosA+cosB+cosC=P2cos(A/2+B/2)cos(A/2-B/2)+1-2sin^c/2=P2sinC/2.cos(A/2-B/2)+1-2sin^C/2=PRearrange it properly2sin^C/2-2sinC/2.cos(A/2-B/2)-1+P=0Quadratic equation in sinC/2 So ∆>=04cos^(A/2-B/2)>=4×2×(P-1)Max value of Cos^(A/2-B/2) is 1Therefore 1>=2P-2 2P
ankit singh
askIITians Faculty 614 Points
8 months ago
iven, cosA + cosB + cosC = 3/2

=> 2(2cos(A + B)/2 . cos(A - B)/2) + 2cosC = 3

=> 2(2cos(pi/2 -c/2) .cos(A - B)/2 + 2(1 - 2sin^2(A/2)) = 3

=> 4sin(c/2) .cos(A - B)/2 + 2 - 4sin^2(A/2)) = 3

=> 4sin^2(A/2) - 4sin(c/2) .cos(A - B)/2 + 1 = 0

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free